AN ANALYSIS OF READABILITY OF READING TEXTS ON ENGLISH NATIONAL EXAMINATION ON JUNIOR HIGH SCHOOL - Noviyanti Lendo; Nihta Liando; Sanerita Olii (Journal of English Culture, Language, Literature and Education, 2021)
This research aims to find out whether texts in the English National Examination at Junior High School. Conform with students' readability level or not. This research is research that uses quantitative methods. It aims to investigate the readability of the texts used in the English national examination texts for junior high school students. Subjects are 8 texts used in the English national examination texts. The instrument used to collect data is the Flesch Reading Ease readability formula. The results of the study it was found that the reading text on the National Examination test was not suitable for junior high school students. Based on the readability formula for the eight reading texts, there are 4 texts in the very easy category, in the easy category there is 1 text, in the quite difficult category there is 1 and there are only 2 reading texts that are suitable for students who are included in the standard category and are fairly easy. For those interested in studying readability, besides Flesch reading ease formula. The writer hopes this research can give more information for further research. The author expected to pay attention to producing better texts which suitable with the level of the students’ readability as the good text can help students to get a high score.